Paraglacial lagoons of Svalbard: emerging ecosystems at the Arctic Land-Sea interface - Sergej Olenin; Jan Kavan; Mateusz C. Strzelecki; Kit M. Kovacs; Christian Lydersen; Guttorm Christensen; Tobia Politi; Dzmitry Lukashanets; Anastasija Zaiko; Jakob Thyrring; Jia-An Ye; Ta-Kang Liu; et al. (Frontiers in Marine Science, 2026)
Rapid glacier retreat across the Arctic is transforming coastal landscapes and generating a growing number of previously non-existent aquatic habitats. In Svalbard, this process has led to the formation and expansion of coastal lagoons, including a substantial proportion of newly emerged paraglacial systems. Despite their increasing abundance, these environments remain poorly represented in Svalbard research and monitoring programs, and their ecological and biogeochemical significance is only beginning to be recognized. Herein we synthesize current knowledge of Svalbard coastal lagoons, integrating perspectives from geomorphology, hydrology, ecology, and biogeochemistry. We propose that these systems form a developmental continuum, ranging from newly formed, glacier-influenced basins to more stable and biologically structured lagoons. Observations from recently studied lagoon systems indicate strong environmental gradients, spatial heterogeneity and dynamic hydrological conditions that support diverse and evolving biological communities across trophic levels. Emerging evidence suggests that Arctic lagoons may function as biogeochemical reactors, including potential sources of methane, while also acting as accumulation zones for contaminants such as microplastics and persistent organic pollutants. At the same time, their ecological role – as biodiversity hotspots, transitional habitats, or stepping-stones for species redistribution – remains insufficiently understood. We identify key knowledge gaps related to lagoon formation, physical dynamics, ecosystem development, and greenhouse gas fluxes and outline a research roadmap for coordinated interdisciplinary investigations. We argue that Svalbard lagoons represent a rapidly expanding nature type that provides a unique opportunity to study ecosystem development under climate change and should be integrated into future Arctic research and assessment frameworks.

An Overview Geoheritage of AlUla, Saudi Arabia: From World Heritage Site to Potential Global Geotourism Destination - Subhajit Sen; Jan Freedman; Ali Hassan Al-Musabeh; Fahad S. Al-Ismail; Mohamed O. Abouelresh (Geoheritage, 2025)

Biotic and Abiotic Factors Shaping the Metacommunity Structure of Free‐Living Bacterioplankton and Nanoflagellates in the Kuroshio Region - Feng‐Hsun Chang; Ariana Chih‐Hsien Liu; Jinny Wu Yang; Hiroaki Saito; Yu Umezawa; Chung‐Chi Chen; Jan Sen; Chih‐hao Hsieh (Molecular Ecology, 2025)
Substantial community variation in free‐living bacterioplankton and their main predators—heterotrophic and mixotrophic nanoflagellates (HNFs)—often remains unexplained due to the frequent oversight of their mutual dependency through reciprocal influences. Here, we sampled bacterioplankton and HNFs from both the surface layer and the deep chlorophyll maximum (DCM) across a 13‐degree latitudinal transect in the Kuroshio, spanning from Taiwan to Japan. Using three‐way variation partitioning complemented by a null model approach, we disentangled the reciprocal influences between these microbial groups alongside the effects of dispersal and the abiotic environment. Our analyses reveal that bacterioplankton and nanoflagellates reciprocally explain over 10% of compositional variation when both layers are analysed together, highlighting the significance of their reciprocal influences. Dispersal contributes a comparable 10% of the explained variation, whereas environmental dissimilarity plays a minor role in shaping both trophic levels. When examining each layer separately, bacterioplankton composition is primarily driven by dispersal, whereas the composition of heterotrophic and mixotrophic nanoflagellates cannot be uniquely attributed to bacterioplankton, dispersal, or environmental factors. These findings suggest that biotic factors become more pronounced when considering vertical variation, whereas horizontal dispersal predominantly drives community composition within a given water layer. By incorporating two trophic levels, this study provides new insights into the metacommunity dynamics of free‐living bacterioplankton and HNFs, emphasising the role of their mutual influences across depth gradients.

Vertical distribution of picoplankton across a cold eddy in the West Pacific Ocean - Patrichka Wei Yi Chen; Madeline Olivia; Chia Mei Chang; Gwo Ching Gong; Chung-Chi Chen; Sen Jan; Clara Natalie Annabel; An Yi Tsai (Frontiers in Marine Science, 2025)
Mesoscale eddies are recognized as an important driver of environmental and microbial dynamics in the Pacific Ocean. However, their specific impact on microbial community vertical distribution remains underexplored. In contrast with the surrounding waters, a cyclonic cold eddy can provide nutrients to the photic zone, increasing primary production and altering microbial communities. A field investigation was conducted in the West Pacific Ocean during cyclonic cold eddy propagation to determine the impact of cold eddies on bacteria and picophytoplankton. Within the cold eddy region, dissolved inorganic nitrate concentrations were higher than those in adjacent water at 100-m depth. Flow cytometric analyses were used to estimate the abundances of picoplankton populations (heterotrophic bacteria and picophytoplankton) in seawater samples collected from the surface to 1,000 m. In this study, Prochlorococcus was the dominant component of abundance at depths above 100 m (62% to 95%). Interestingly, when compared to outside of eddy stations, cyclonic eddy-affected regions had the lowest maximum value of Synechococcus and Prochlorococcus . In contrast to Synechococcus and Prochlorococcus , the distribution pattern of picoeukaryotes abundance showed maxima values (>0.4 × 10 3 cells mL −1 ) at 100–200-m depth within cyclonic eddy-affected regions. Overall, the abundance of bacteria was approximately 2 × 10 5 cells mL −1 at the surface and increased to >4 × 10 5 cells mL −1 at 200-m depth at stations outside the eddy. However, peaks in bacterial abundance were observed at 50-m depth, and abundance decreased with increasing depth in the cyclonic eddy-affected regions. In the oligotrophic open ocean, our findings contribute to a better understanding of the biological response of mesoscale eddies.

Small eukaryotic plankton community and alpha diversity variability in the Kuroshio region - Ariana Chih-Hsien Liu; Feng-Hsun Chang; Jinny Wu Yang; Hiroaki Saito; Yu Umezawa; Chung-Chi Chen; Sen Jan; Chih-hao Hsieh (Marine Environmental Research, 2025)

Connection of central South China Sea current variability with tropical Rossby waves in the western North Pacific - Mac Euan D. Malugao; Sen Jan; Ming-Huei Chang; Tung-Yuan Ho; Yiing Jang Yang (Progress in Oceanography, 2025)

Distinct water mass between inside and outside eddy drive changes in prokaryotic growth and mortality in the tropical Pacific Ocean - Patrichka Wei-Yi Chen; Madeline Olivia; Gwo-Ching Gong; Sen Jan; Tung-Yuan Ho; Louis St. Laurent; An-Yi Tsai (Frontiers in Marine Science, 2024)
Throughout the western tropical Pacific Ocean, eddies and currents play an important role in biogeochemical cycling. Many studies have investigated the effects of hydrography on vertical patterns of picophytoplankton and heterotrophic bacterial abundance in mesoscale eddies. There is a lack of field observations to determine what impact dynamic hydrological systems of eddies have on prokaryotic community activity (growth and mortality rates). An objective of this study was to examine how anticyclonic eddies influence picoplankton abundance and activity (growth and mortality rates). To meet this purpose, heterotrophic bacterial and picophytoplankton growth and mortality rates were examined by modified dilution experiments conducted at the surface, deep chlorophyll maximum (DCM), and 200 m depth outside (OE) and inside of warm eddies core (EC) in the west Pacific Ocean. A high heterotrophic bacterial grazing rate was found in the EC region in the present study. Furthermore, the picophytoplankton grazing rate in EC was frequently greater than the grazing rate in OE. Furthermore, the higher grazing rates in the EC region cause a lower proportion of viral lysis to account for heterotrophic bacteria and picophytoplankton mortality. The results of our experiments suggest that downwelling in EC might increase picophytoplankton growth and grazing rates, increasing the carbon sink in the warm eddy and potentially increasing ocean carbon storage.

Rational design of crystalline/amorphous nickel manganese phosphate octahydrate heterostructure for high-performance aqueous and all-solid-state asymmetric supercapacitors - Min Li; Min Li; Mingshu Zhao; Bing Wu; Stefanos Mourdikoudis; Shuangying Wei; Filipa M. Oliveira; Junjie He; Lukáš Děkanovský; Jan Luxa; Sen Yang; Zdeněk Sofer (Chemical Engineering Journal, 2024)

Kuroshio Intrusion and Its Impact on Swordtip Squid (Uroteuthis edulis) Abundance in the Southern East China Sea - Yi-Chen Cheng; Sen Jan; Chung-Chi Chen (Frontiers in Marine Science, 2022)
Swordtip squid ( Uroteuthis edulis ) is a primary target species of the commercial fishery in the southern East China Sea (ECS), and they normally migrate to a quasi-permanent upwelling zone (called a cold dome) off northeastern Taiwan for spawning and growth during spring (March–May) and fall (October–December) in a year. We examined the connection of the variability in its standardized annual catch per unit effort (CPUE) during 2009–2017 in regard to the physical processes on the southern shelf of the ECS using temperature and wind observations from an isle north of Taiwan (Peng-jia-yu) as well as satellite sea surface temperature and absolute geostrophic velocity. The annual CPUE is positively correlated with the daily temperature anomaly at Peng-jia-yu in the cold dome in October of the previous year and April of the year. A warmer environment favors the recruitment and consequently the catch of the swordtip squid. During the spawning periods of the 9 years, the warm water carried by the Kuroshio frequently intruded atop the cold dome, which benefited the growth of the larvae and consequently helped maintain a certain value of the standardized annual CPUE. The anomalously low CPUE in 2012 and 2016 is attributed to the blocking of the Kuroshio intrusion due to cold and less salty China Coastal Water atop the cold dome in the spring spawning of 2012 and 2016. Based on the velocity strength in the cold dome and in a specified shelf region together with the daily temperature anomaly at Peng-jia-yu, an occupation intensity factor is used to evaluate the dominance of warm Kuroshio water and cold shelf water in the cold dome, which could help predict annual catches.

Shear Instability and Turbulent Mixing in the Stratified Shear Flow Behind a Topographic Ridge at High Reynolds Number - Jia-Lin Chen; Xiao Yu; Ming-Huei Chang; Sen Jan; Yiing Jang Yang; Ren-Chieh Lien (Frontiers in Marine Science, 2022)
Observations on the lee of a topographic ridge show that the turbulence kinetic energy (TKE) dissipation rate due to shear instabilities is three orders of magnitude higher than the typical value in the open ocean. Laboratory-scale studies at low Reynolds number suggest that high turbulent dissipation occurs primarily within the core region of shear instabilities. However, field-scale studies indicate that high turbulence is mainly populated along the braids of shear instabilities. In this study, a high-resolution, resolving the Ozmidov-scale, non-hydrostatic model with Large Eddy Simulation (LES) turbulent closure is applied to investigate dominant mechanisms that control the spatial and temporal scales of shear instabilities and resulting mixing in stratified shear flow at high Reynolds number. The simulated density variance dissipation rate is elevated in the cusp-like bands of shear instabilities with a specific period, consistent with the acoustic backscatter taken by shipboard echo sounder. The vertical length scale of each cusp-like band is nearly half of the vertical length scale of the internal lee wave. However, it is consistent with instabilities originating from a shear layer based on linear stability theory. The model results indicate that the length scale and/or the period of shear instabilities are the key parameters to the mixing enhancement that increases with lateral Froude number Fr L , i.e. stronger shear and/or steeper ridge.

Effects of the Coastal Uplift on the Kuroshio Ecosystem, Eastern Taiwan, the Western Boundary Current of the North Pacific Ocean - Chung-Chi Chen; Chun-Yi Lu; Sen Jan; Chih-hao Hsieh; Chih-Ching Chung (Frontiers in Marine Science, 2022)
The Kuroshio is the western boundary current of the North Pacific Ocean. In the subtropical region of eastern Taiwan, a coastal uplift of the isotherms has occurred. To explore its impact on this oligotrophic ecosystem, hydrographic data along the transect line at 23.75°N were measured between September 2012 and September 2014. Results show that the intensity of coastal uplift was positively correlated to the flow volume transport of the Kuroshio. Significant dissolved inorganic nutrients were uplifted to the sunlit zone, especially in the onshore. For example, compared to the offshore, nitrate concentration increased 0.49 μM (or ∼178%) in the upper 100 m of the onshore. The increased nutrients thereafter enhanced the growth of phytoplankton; for instance, the Chl a concentration increased 88.3%, compared to offshore, in the upper 100 m of the onshore. Phytoplankton community was mostly composed of picophytoplankton (<2 μm in size), which were dominated, in terms of relative abundance, by Prochlorococcus (83.6%), followed by Synechococcus (13.8%) and picoeukaryotes (2.7%). The relative abundance of Prochlorococcus increased from onshore toward offshore, but the trend was reversed for Synechococcus and picoeukaryotes, which may be affected by the coastal uplift. The results also suggest that the coastal uplift may support more energy transferred to higher tropical levels in this oligotrophic Kuroshio ecosystem.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Response of the Kuroshio east of Taiwan to mesoscale eddies and upstream variations - Vigan Mensah; Sen Jan; Magdalena Andres; Ming-Huei Chang (Journal of Oceanography, 2020)

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Using major nutrient concentrations to derive vertical movement of water masses in the coastal region of eastern Taiwan - Su-Cheng Pai; Sen Jan; Tung-Yuan Ho; Jin-Yuan Liu; Ken-Sheng Chu; Wen-Huei Lee; Cheng-Yun Wang; Ping-Yi Huang; Hung-Yu Hsu; Yiing-Jang Yang (Journal of Oceanography, 2017)

Mean Structure and Variability of the Kuroshio from Northeastern Taiwan to Southwestern Japan - Magdalena Andres; Sen Jan; Thomas Sanford; Vegan Mensah; Luca Centurioni; Jeffrey Book (Oceanography, 2015)

Mean Structure and Fluctuations of the Kuroshio East of Taiwan from In Situ and Remote Observations - Ying Jang Yang; Sen Jan; Ming-Hueh Chang; Joe Wang; Vegan Mensah; Tien-Hsia Kuo; Cheng-ju Tsai; Chung Yaung Lee; Magdalena Andres; Luca Centurioni; Yu-Heng Tseng; Wen-Der LIang; et al. (Oceanography, 2015)

Two Mechanisms Cause Dual Velocity Maxima in the Kuroshio East of Taiwan - Kai-Chieh Yang; Joe Wang; Craig Lee; Barry Ma; Ren-Chieh Lien; Sen Jan; Ying Jang Yang; Ming-Huei Chang (Oceanography, 2015)

A New Look at Circulation in the Western North Pacific: Introduction to the Special Issue - Daniel Rudnick; Sen Jan; Craig Lee (Oceanography, 2015)

Erratum to: Screening for new sources of resistance to Clavibacter michiganensis subsp. michiganensis (Cmm) in tomato - Yusuf Sen; Feng Zhu; Henri Vandenbroucke; Jan van der Wolf; Richard G. F. Visser; A. W. van Heusden (Euphytica, 2013)

Screening for new sources of resistance to Clavibacter michiganensis subsp. michiganensis (Cmm) in tomato - Yusuf Sen; Zhu Feng; Henri Vandenbroucke; Jan van der Wolf; Richard G. F. Visser; A. W. van Heusden (Euphytica, 2013)

Circulation and Intrusions Northeast of Taiwan: Chasing and Predicting Uncertainty in the Cold Dome - Glen Gawarkiewicz; Sen Jan; Pierre Lermusiaux; Julie McClean; Luca Centurioni; Kevin Taylor; Bruce Cornuelle; Timothy Duda; Joe Wang; Yiing Jiang Yang; Thomas Stanford; Ren-Chieh Lien; et al. (Oceanography, 2011)

Mean Structure and Variability of the Cold Dome Northeast of Taiwan - Sen Jan; Chung-Chi Chen; Ya-Ling Tsai; Yiing Jiang Yang; Joe Wang; Ching-Sheng Chern; Glen Gawarkiewicz; Ren-Chieh Lien; Luca Centurioni; Jia-Yu Kuo (Oceanography, 2011)

Seasonal and Mesoscale Variability of the Kuroshio Near Its Origin - Daniel Rudnick; Sen Jan; Luca Centurioni; Craig Lee; Ren-Chieh Lien; Joe Wang; Dong-Kyu Lee; Ruo-Shan Tseng; Yoo Yin Kim; Ching-Sheng Chern (Oceanography, 2011)

Short‐term dynamics of oxygen and carbon in productive nearshore shallow seawater systems off Taiwan: Observations and modeling - Zong-Pei Jiang; Jr-Chuan Huang; Minhan Dai; Shuh Ji Kao; David J. Hydes; Wen-Chen Chou; Sen Jan (Limnology and Oceanography, 2011)
The diurnal to weekly dynamics of carbon and oxygen in two productive tropical–subtropical nearshore shallow water systems were investigated using a combination of time‐series observation and modeling. The two sites, Aodi (121.93°E, 25.06°N) and Nanwan (120.85°E, 21.91°N), were characterized by limited freshwater input, strong tidal advection and, at Nanwan, upwelling. The diurnal ranges were 96–234 µmol kg −1 for dissolved inorganic carbon (DIC), 8.9–42.2 Pa for partial pressure of carbon dioxide ( p CO 2 ), and 37–239 µmol kg −1 for dissolved oxygen. The diurnal variability increased from spring to neap tidal states at both sites. A model accounting for gas exchange, biological activities, tidal advection, and upwelling was developed to assess the biophysical interactions modulating the biogeochemical dynamics. The strongest driver of the diurnal variability was the net ecosystem production of the benthic‐dominated nearshore ecosystem. Tidal advection buffered the accumulation of biological effects and the intensified dispersion lowered the diurnal amplitudes at spring tides. Tide‐induced upwelling at Nanwan increased the surface inorganic carbon, and its decreasing intensity resulted in declines in DIC and p CO 2 from spring toward neap tide. The maximum community photosynthetic rates at Aodi and Nanwan were 295 and 120 mmol C m −2 h −1 , with ecosystem respiratory rates of 122 and 53 mmol C m −2 h −1 . The two autotrophic ecosystems were sinks for atmospheric CO 2 during the study period, with the average air–sea fluxes being −0.30 and −0.56 mmol C m −2 d −1 for Aodi and Nanwan.

Numerical study of mean flow patterns in the South China Sea and the Luzon Strait - Ching-Sheng Chern; Sen Jan; Joe Wang (Ocean Dynamics, 2010)

Sources of water in the Taiwan Strait - Sen Jan; Yu-Heng Tseng; David E. Dietrich (Journal of Oceanography, 2010)

Green tea extract protects rats against myocardial infarction associated with left anterior descending coronary artery ligation - Shih-Rong Hsieh; Dan-Chin Tsai; Jan-Yow Chen; Sen-Wei Tsai; Ying-Ming Liou (Pflügers Archiv - European Journal of Physiology, 2009)

Numerical study of baroclinic tides in Luzon Strait - Sen Jan; Ren-Chieh Lien; Chi-Hua Ting (Journal of Oceanography, 2008)

Transition of Tidal Waves from the East to South China Seas over the Taiwan Strait: Influence of the Abrupt Step in the Topography - Sen Jan; Ching-Sheng Chern; Joe Wang (Journal of Oceanography, 2002)

Circulation and Brackish Water Dispersal in a Coastal Lagoon of Southwest Taiwan - Sen Jan; Shenn-Yu Chao; Jia-Jang Hung (Journal of Oceanography, 2001)

Nutrient Fluxes through the Taiwan Strait in Spring and Summer 1999 - Shi-Wei Chung; Sen Jan; Kon-Kee Liu (Journal of Oceanography, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)